Are customers' reviews creating value in the hospitality industry? Exploring the moderating effects of market positioning. Issue 6 (December 2016) - Neirotti, Paolo; Raguseo, Elisabetta; Paolucci, Emilio
Highlights: Social Media and user-generated reviews are transforming competition in the hospitality industry. On-line ratings of user-generated reviews on TripAdvisor have a positive effect on hotel revenues that is outweighed by a negative effect on gross profit margins. Hotels placed outside popular destinations get more advantages from their online visibility on their gross and net profitability than hotels placed in popular destinations. Hotels with higher star-rating get more benefits from online visibility on their gross and net profitability. Hotels with a lower degree of local competition get more benefits from online visibility on their gross and net profitability. Abstract: Although user-generated reviews on social media are greatly influencing competition and customer purchase patterns in the hospitality industry, empirical research has so far marginally investigated whether hotels are able to appropriate the economic value that the use of social media features can bring. In order to fill this gap, this article uses panel data from 2004 to 2012 on a sample of 240 small and medium-sized hotels for which we have collected data on profitability and 50, 115 user-generated reviews on TripAdvisor, one of the most popular and largest online community for travellers. The results from fixed effects regression models show that online ratings from user-generated reviews on TripAdvisor have a positive effect on hotel revenue growth that is outweighed by a negative effect on gross profit margins. Thus, the increasing importance of user-generated reviews in online communities for travellers is shifting hotel competition from unit profit margin to volumes and to higher room occupancy rates, with online retailers capturing most of the value created in online transactions through social media features and with a limited effect brought on net profitability. However, hotels with higher star-rating, with a lower degree of local competition and localized outside popular destinations were found to obtain more benefits from online visibility on their gross and net profitability. Based on these results, managerial implications discuss how hotels should use social media features according to a strategic view based on pursuing the horizontal and vertical differentiation of their services in an attempt to create more economic value from their online visibility and to protect profit margins from the intermediation in their customer relationships.